Exploring Optimal Cereal Crop Sequence Using Cultivated Land Utilization Index and Yield in Katihar District, India: A Sub Division Level Analysis - Mandal, Vinay Prasad; Ahmad, Raihan; Rehman, Sufia; Masroor, Md; Sajjad , Haroon (Asian Journal of Agriculture and Rural Development, 2019)
The present study attempts to identify the suitable crop sequences in an agriculturally productive district of Bihar, India. Rice-rice-vegetables, rice-maize-rice, rice-maize-maize, rice-maize-jute, rice-pulse-rice, rice-pulse-jute, rice-pulse-potato, and maize-maize-rice were found to be the suitable crop sequences in the area under study. Findings revealed that most of the blocks were found suitable for suggested crop sequences, while only two blocks (namely Balrampur and Barsoi) showed low potential in the rice-maize-rice sequence. Use of farm machinery, application of efficient farm inputs, and irrigation is required to maximize the yield and achieve long-term agricultural sustainability in this district.